2021
DOI: 10.3389/fonc.2020.603702
|View full text |Cite
|
Sign up to set email alerts
|

Bcl9 Depletion Modulates Endothelial Cell in Tumor Immune Microenvironment in Colorectal Cancer Tumor

Abstract: Tumor endothelial cells are an important part of the tumor microenvironment, and angiogenesis inhibitory therapy has shown potential in tumor treatment. However, which subtypes of tumor endothelial cells are distributed in tumors, what are the differences between tumor endothelial cells and normal endothelial cells, and what is the mechanism of angiogenesis inhibitory therapy at the histological level, are all need to be resolved urgently. Using single-cell mRNA sequencing, we analyzed 12 CT26 colon cancer sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…We therefore further analyzed the balance of Ig at the clinical and genetic levels. We constructed the HeavytoLight score to evaluate the balance of Ig light-and heavy-chain gene expression (Wei et al, 2020(Wei et al, , 2021. The liver-metastatic group had lower HeavytoLight scores than the nonmetastatic group (p = 0.037) (Figure S7A), which was consistent with our scRNA-seq observations.…”
Section: Characteristics Of Patients With Colon Cancer With or Withou...supporting
confidence: 84%
“…We therefore further analyzed the balance of Ig at the clinical and genetic levels. We constructed the HeavytoLight score to evaluate the balance of Ig light-and heavy-chain gene expression (Wei et al, 2020(Wei et al, , 2021. The liver-metastatic group had lower HeavytoLight scores than the nonmetastatic group (p = 0.037) (Figure S7A), which was consistent with our scRNA-seq observations.…”
Section: Characteristics Of Patients With Colon Cancer With or Withou...supporting
confidence: 84%
“…Among them, cluster 23 was composed mainly of BRCA, and cluster 5 was composed mainly of BRCA, Uterine Corpus Endometrial Carcinoma (UCEC), and Cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC). According to our previous reports, cluster 5 had marker genes TYR and MLANA (Wei et al, 2020). These results suggested that TYR and MLANA may be used as pathological criteria for prognostic prediction with TAM-to-NK score.…”
Section: Low Tumor-associated Macrophages-to-nk Score Predicts Poor Prognosis In Cancer Patientssupporting
confidence: 58%
“…After completing the principal component analysis of genes, UMAP, which is a dimensionality reduction method based on manifold analysis, grouped the cells together according to the similarity of gene expression (Figure 2A). Through the clustering analysis of all cells, we found that these cells can be divided into eight clusters corresponding to tumor cells, tumor-associated monocytes, TAMs, tumor-associated endothelial cells, fibroblasts, and T cells (Figure 2A), these classifications are based on known markers or bioinformatics research (Wei et al, 2020). To study the potential differences in TAMs, we extracted the TAM population based on the cell information we previously reported (Wei et al, 2020), and performed re-clustering analysis (Step 1 re-clustering; Figures 2B-E).…”
Section: Single-cell Rna-seq Of Mouse Ct26 Tumor With Pharmacological Inhibition Of Bcl9 and Genetic Depletion Of Bcl9mentioning
confidence: 99%
See 2 more Smart Citations